Woman Self Defense Portrayed on Jane Green’s Jemima J: An Approach to Psychoanalysis Abraham Maslow - Ifa Nurdiana; Wilujeng Asih Purwani (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
This study is aimed to interpret the self-defense behaviors carried out by lead figures, Jemima Jones in Jane Green’s novel Jemima J (1998) through the theory of psychoanalysis by Abraham Maslow’s which focuses on the love and belonging level. This study employs qualitative literary analysis methodology. It identifies and interprets textual evidence illustrating how the protagonist character did not meet the need for love and belonging leads her emotion, behavior, and self-acceptance. The finding of this research shows Jemima’s has some strategies to cope the unmet need of love and belonging such as compulsive overeating, romanticized fantasizing, and internet dating behaviors. It is consistent with Maslow’s deficiency motivation theory. Further, the finding is supported by empirical research on emotional eating, body image, and social belonging, placing the literary analysis within a wider discourse of psychology. This study contributes to the expanding application of humanistic psychology in literary criticism and highlights the novel’s relevance to current discussion of body image, social connection, and emotional well-being.